Eve as Cyborg. Issue 2 (3rd March 2021) - Conway, Colleen M.
Abstract : The essay argues that the figure of the female cyborg introduced by Donna Haraway has yet to live up to its post-gender emancipatory promise. Both Haraway and Jack Halberstam contrast the female cyborg with the biblical Eve and her mythic origins in the garden of Eden. I argue that the figure of Eve is actually an ancient precursor to the female cyborg. Even more than the Greek myth of Pygmalion, the Eden myth shares common elements with later stories of man-made women. Like them, Eve was made to satisfy male desire, but then followed her own desires. Like later stories of female cyborgs, the representation of Eve reflects both male desire and male fear. After analyzing both Ovid's Pygmalion and Genesis 2-3, I trace common elements through the nineteenth century science fiction novel L'Eve future and the twenty-first century film Ex Machina. Like Eve, the female cyborgs in these works are built in a garden and their "emancipation" occurs only within the confines of androcentric heteronormative gender patterns.